Le Mahdi dans le Maghreb médiéval - Michael Brett (Université de Provence, 2000)
North Africa was the great center of Mahdism in mediaeval Islam, where it inspired two out of the three great revolutions that progressively unified the Maghrib between the 4th/10th and 6th/12th centuries : the Fatimid in the tenth and the Almohad in the 12th. The Islamic form of Judaeo-Christian Messianism, Mahdism, looked for the coming of a second Muhammad to inaugurate an era of righteousness, but it shared the same uncertainty over a kingdom of this world or the next, over a « man sent from God »or a divine being. Success in the Maghrib came from a call to empire, achieved by militant preaching to tribal peoples induced to submit to the military discipline of a prophet. In both cases, however, the preaching and its fulfilment were divided between two figures : a John the Baptist-like herald and the « man bom to be king ». In the case of the Fatimids, the king was the Mahdi himself, but in the case of the Almohads, the Mahdi was the prophet who opened the way for his Caliph, the appointed ruler of the world. After the break-up of the Almohad empire in the thirteenth century, Mahdism in the Maghrib lapsed into ineffective millenarianism, but returned to power in the 16th century with the Saadian dynasty in Morocco. Both then and in the 19th century, in the case of Abdelkader in Algeria, it conformed to the same pattern of prophet and king. But in the course of the 20th century, Mahdism has been overtaken by nationalism as an effective political force.